Enhance Similarity Measure of Ontologys' Concepts (Journal of the College of Education for Women, 2019)
The field of identification of similarity was considered a subject of research strongly recommended in the areas of semantic web, artificial intelligence and linguistic literature. In this paper a new similarity measure is proposed based on the Wu and Palmer measure. This measure is applied on the domain of the pedagogical ontology. Results obtained showed that the new measure gives better relevance of the similarity values compared to the approach of Wu and Palmer and it appears that the proposed measure is advantageous because obtained results showed that it is faster and capable of obtaining results to concepts not located in the same path.